1999
DOI: 10.1111/1475-3588.00270
|View full text |Cite
|
Sign up to set email alerts
|

Children as Service Evaluators

Abstract: In recent years there has been a growing interest in methods of eliciting children's views on factors influencing their lives. When children's views are sought it is important that this is done in a developmentally appropriate manner with instruments whose psychometric properties are known. The present review describes a variety of methods that have been used to evaluate children's satisfaction with services in education, paediatrics and mental health. The majority of the studies used self‐completion questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…All the suggestions made by Pyramid attendees indicate the importance of ensuring that service user satisfaction evaluations incorporate measures and methods that are salient to the children in their role by identifying what their needs and expectations are and acting upon them (Day et al, 2006;Hennessy, 1999). Furthermore, in support of prior research (Ohl et al, 2012, Ohl et al, 2008 this study suggests that Pyramid offers socio-emotionally vulnerable children an opportunity to practice social skills and gain confidence facilitated by supportive and approachable adults in a familiar school-based setting.…”
Section: How Pyramid Clubs Might Be Developedmentioning
confidence: 61%
See 1 more Smart Citation
“…All the suggestions made by Pyramid attendees indicate the importance of ensuring that service user satisfaction evaluations incorporate measures and methods that are salient to the children in their role by identifying what their needs and expectations are and acting upon them (Day et al, 2006;Hennessy, 1999). Furthermore, in support of prior research (Ohl et al, 2012, Ohl et al, 2008 this study suggests that Pyramid offers socio-emotionally vulnerable children an opportunity to practice social skills and gain confidence facilitated by supportive and approachable adults in a familiar school-based setting.…”
Section: How Pyramid Clubs Might Be Developedmentioning
confidence: 61%
“…Hennessy's (1999) review of methods to establish children's satisfaction with child and adolescent health services in the United Kingdom (UK) reported that very few measures relate directly to the children themselves with most items being generated by parents or clinicians. This may be due to the perception that there exists a critical age at which children can independently express their viewpoint reliably.…”
Section: Introductionmentioning
confidence: 99%
“…Many instruments are now available (e.g. see, Attride-Stirling, 2003;Hennessy, 1999). Notwithstanding the well-recognized methodological flaws of service satisfaction evaluation, such as sampling bias, low response rates and CLINICAL CHILD PSYCHOLOGY AND PSYCHIATRY 11(1) 140 C R I S P I N DAY has responsibility for the strategic and clinical development of community child mental health services in Southwark, London.…”
mentioning
confidence: 99%
“…This has undoubtedly contributed to and been fuelled by the United Nations Convention on the Rights of the Child (Lü cker-Babel, 1995). In many spheres the significance of the child's voice finds greater recognition: in service evaluation (Hennessy, 1999); in planning and decision making (Sinclair, 1998); in researching children's experience (Hogan and Gilligan, 1998). While much has changed, clearly there is more work to be done in terms of adjusting professional practices in, for example, the conduct of care reviews to better reflect the understanding, concerns and preferences of young people (Grimshaw and Sinclair, 1997).…”
Section: Social Work Services and Children In Care 269mentioning
confidence: 99%